Implementasi Supervisi Pendidikan dalam Meningkatkan Kinerja Guru - Muh. Muchlis; Heldy Ramadhan Putra P (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the work program of supervision, implementation of supervision, and the constraints of school principals in implementing educational supervision. This type of research uses descriptive qualitative with a case study research design that focuses on teacher performance. The research subjects included the principal, vice-principal/Guardian Angel (GA), and classroom teachers at MIM PK Kartasura. The main data collection is done through observation, interviews, and documentation. Data analysis procedures are data reduction, data display, and verification. The results showed: (1) The educational supervision work program carried out by the head of the MIM PK Kartasura Madrasah already had a good design for the next one year period and was reformulated in the coming year; (2) The implementation of educational supervision implemented by the head of MIM PK Kartasura is carried out with a direct approach. Assessment of educational supervision is compiled in the form of a teacher report card. There are three forms of educational supervision at MIM PK Kartasura, namely plan to lesson/RPP assessment, teaching supervision, and disciplinary assessment, (3) Obstacles faced by school principals in the implementation of educational supervision, among others; (a) educational supervision approach, the principal has little time so that the implementation of supervision is difficult to synchronize, (b) educational supervision techniques, paying more attention to the psychological aspects of teachers and this factor greatly determines the implementation of the educational supervision program, and (c) behavior teachers at the time of educational supervision, the conditions of the teachers were very varied and highly dependent on the techniques used by the principal. Keywords: education supervision, teacher performance